Pressão arterial em crianças e adolescentes atendidos no ambulatório de obesidade infantil da Fundação Santa Casa de Misericórdia do Pará. - VENTURIERI, Maissara Obara (2022)
Introduction: The measurement of blood pressure is the most important procedure for the identification of high blood pressure (HBP), whose diagnosis is performed more frequently in patients with advanced age, but its onset may occur in childhood. It is a disease that results from multifactorial causes, notably obesity as a major risk factor. Objectives: To assess the blood pressure in children and adolescents in outpatient follow-up of obesity. Patients and Methods: Observational and prospective study of blood pressure in 90 children and adolescents from 7 to 17 years of age, followed in the clinic of obesity in the period September 2007 to May 2008. Blood pressure was measured using the parameters set by the Fourth Report (2004) and the V Brazilian Guidelines on Hypertension (2006). We studied the following variables: age, sex, body mass index, socioeconomic level, family history, birth weight, duration of exclusive breastfeeding and the habit of adding salt to the diet. For comparison of proportions were used non-parametric tests: chi-square, McNemar and parametric tests: Student t test for related samples with a significance level of 5%. Results: The overall mean systolic blood pressure was 100.34 ± 8.38 mmHg and diastolic 61.33 ± 9.55 mmHg, and 4.4% prevalence of white-coat hypertension and 2.2% prevalence of hypertension (p = 0.0001). The age range of 7 to 12 years (83.3%) was statistically significant (p = 0.0001). The obesity was 44.4% overweight and 46.7%. Most were founded in the metropolitan area of Belém and economic classes C and D. The appropriate weight at birth was present in 59.2% (p = 0.0001), breastfeeding for at least 6 months in 57% (p = 0.0001) and not have the habit of adding salt to food at 68 % (p = 0.0026). Conclusion: There was a low prevalence of hypertension despite the relevance of it. Overweight and obesity were groups with similar percentages. A normal blood pressure was associated with the appropriate weight at birth, to breastfeeding for at least 6 months and the habit of not adding salt to the diet. Reducing the prevalence of hypertension was directly related to a greater number of consultations, but no significant variation between the pressure levels measured in a single query.